2013
DOI: 10.1116/1.4774061
|View full text |Cite
|
Sign up to set email alerts
|

Metal contact printing photolithography for fabrication of submicrometer patterned sapphire substrates for light-emitting diodes

Abstract: This paper reports an improved method that combines a metal film contact printing method with traditional photolithography for fabrication of submicrometer-scale patterned sapphire substrates (PSSs) used for high-brightness light-emitting diodes (LEDs). First, a patterned metal thin film is transferred from the surface of a mold onto a photoresist (PR) layer deposited on top of the sapphire substrate. The transferred metal pattern acts as a photomask for subsequent photolithographic processes. PR structures wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The PSS can get more photons generated in the active layer into the air to enhance the LEE. [7,8] To date, different types and morphologies of PSS, from micropatterns to nanopatterns, such as cone-shaped PSS, [9] pyramidally PSS, [10,11] volcano-shaped PSS, [12,13] micro-hole patterns, [14] concave-hexagonal PSS, [15] lensshaped PSS, [16] have been employed in use of GaN-based LEDs. The micro-patterned sapphire substrates (MPSSs) show great performance in both enhancing the LEE and reducing the TD.…”
Section: Introductionmentioning
confidence: 99%
“…The PSS can get more photons generated in the active layer into the air to enhance the LEE. [7,8] To date, different types and morphologies of PSS, from micropatterns to nanopatterns, such as cone-shaped PSS, [9] pyramidally PSS, [10,11] volcano-shaped PSS, [12,13] micro-hole patterns, [14] concave-hexagonal PSS, [15] lensshaped PSS, [16] have been employed in use of GaN-based LEDs. The micro-patterned sapphire substrates (MPSSs) show great performance in both enhancing the LEE and reducing the TD.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical and experimental studies 7,8 have suggested that greater light output power (LOP) may be achieved for GaN-based LEDs when nanopatterned sapphire substrates (NPSSs) are used rather than micropatterned sapphire substrates (MPSSs). In recent studies, various state-of-the-art techniques, such as e-beam lithography, 10 metal contact printing photolithography, 11 nanoimprint lithography (NIL), 12 and nanosphere lithography 13 have been used to fabricate NPSSs. 9 However, contact photolithography, which is used for production of MPSSs, is not suitable for patterning in the submicrometer range.…”
Section: Introductionmentioning
confidence: 99%